Impact of Race and Geographic Area of Residence on Outcomes After Allogeneic Stem Cell Transplant - Sigmund, Audrey M.; Zhao, Qiuhong; Jiang, Justin; Elder, Patrick; Benson, Don M.; Rosko, Ashley; Bumma, Naresh; Khan, Abdullah; Devarakonda, Srinivas; Vasu, Sumithira; Jaglowski, Samantha; Mims, Alice; et al. (Frontiers in Oncology, 2022)
Background Allogeneic hematopoietic stem cell transplant (allo-HCT) is a potential curative therapy for a variety of hematologic disorders. However, it requires highly specialized care that is only available at select centers across the country. Thus, minority populations are at risk for healthcare disparities in access to and outcomes of allo-HCT. Our study aimed to assess the impact of race and location of residence on outcomes of allo-HCT. Methods We performed a retrospective analysis of all patients who underwent allo-HCT at the Ohio State University from 1984 to 2018. Patients were divided by race (Caucasian, African American, and other) and grouped by zip code into rural, suburban, and urban groups. Primary endpoints included progression-free survival (PFS) and overall survival (OS). Results Of the 1,943 patients included in the study, 94.3% self-identified as Caucasian, 4.6% African American, and 1.1% other. In total, 63.4% lived in rural areas, 22.9% suburban, and 13.8% urban. There was no significant difference in OS or PFS by race (p = 0.15, 0.21) or place of residence (p = 0.39, 0.17). In addition, no difference in nonrelapse mortality, acute and chronic graft-versus-host disease (GVHD), and GVHD-free relapse-free survival (GRFS) was seen among the race or place of residence. Conclusion Our study suggests that when appropriate access to HCT is given, there is no difference in outcomes based on race, ethnicity or place of primary residence. Further research is needed to further evaluate barriers for these patients to undergo transplant and help mitigate these barriers.